Deteksi Dini Tingkat Risiko Buta Warna dengan Metode Ishihara pada Anak SDN 191 Maluku Tengah - Jusuf Leiwakabessy; Farah Ch. Noya; Johan B. Hutagalung; Gustino Anjelo Bastian; Reka Febriani; Carl Hein Huwaa (Jurnal Pengabdian Masyarakat, 2025)
Color blindness is an X-linked genetic disorder that affects the ability to distinguish certain colors. Although it does not cause total blindness, color vision deficiency can impair the academic performance of elementary school children who rely heavily on color-based learning materials. The lack of public awareness and the limited implementation of vision screening programs in schools have led to many undetected cases of color blindness. This study aims to identify the level of color blindness risk among students at SDN 191 Central Maluku using the Ishihara method, as well as to raise awareness of the importance of early detection of color perception disorders. This study employed a descriptive observational design with a cross-sectional approach. A total of 49 students were included as participants. The examination results were analyzed using descriptive quantitative methods to determine the proportion of students with varying levels of color vision ability.The results showed that 42 students (85.7%) had normal color vision, while 7 students (14.3%) exhibited partial color blindness, with no cases of total color blindness identified. The prevalence was higher among male students (23.1%) compared to females (4.3%), consistent with the X-linked inheritance pattern. Therefore, the Ishihara method is an effective, simple, and practical screening tool for the early detection of color vision deficiency in primary educational settings. The implementation of routine color vision screening in schools is recommended to promote a more inclusive and preventive health-oriented learning environment.